(untitled) (Journal of Computational Mathematics, 1993)
The paper considers the L^∞ convergence for nonconforming finite elements, such as Morley element, Adini element and De Veubeke element, solving the boundary value problem of the bihamonic equation. The nearly optimal order L^∞ estimates are given.